Hepatitis B Surface Antigen Suppresses the Activation of Nuclear Factor Kappa B Pathway via Interaction With the TAK1-TAB2 Complex - Deng, Feiyan; Xu, Gang; Cheng, Zhikui; Huang, Yu; Ma, Caijiao; Luo, Chuanjin; Yu, Chen; Wang, Jun; Xu, Xiupeng; Liu, Shi; Zhu, Ying (Frontiers in Immunology, 2021)
Chronic hepatitis B is a major health problem worldwide, with more than 250 million chronic carriers. Hepatitis B virus interferes with the host innate immune system so as to evade elimination via almost all of its constituent proteins; nevertheless, the func-tion of HBsAg with respect to immune escape remains unclear. This study aimed to determine the role HBsAg plays in assisting HBV to escape from immune responses. We found that HBsAg suppressed the activation of the nuclear factor kappa B (NF-кB) pathway, leading to downregulation of innate immune responses. HBsAg interacted with TAK1 and TAB2 specifically, inhibiting the phosphorylation and polyubiquitina-tion of TAK1 and the K63-linked polyubiquitination of TAB2. Autophagy is a major catabolic process participating in many cellular processes, including the life cycle of HBV. We found that HBsAg promoted the autophagic degradation of TAK1 and TAB2 via the formation of complexes with TAK1 and TAB2, resulting in suppression of the NF-κB pathway. Expression TAK1, TAB2, and the translocation of NF-κB inversely correlated with HBsAg levels in clinical liver tissues. Taken together, our findings suggest a novel mechanism by which HBsAg interacts with TAK1-TAB2 complex and suppresses the activation of NF-κB signaling pathway via reduction of the post-translational modifications and autophagic degradation.